Idiopathic scrotal calcinosis: A rare entity and a review of the literature - Pompeo, Alexandre; Molina, Wilson; Pohlman, Garrett; Sehrt, David; Kim, Fernando (Canadian Urological Association Journal, 2013)
Scrotal calcinosis is a rare condition with presentation includingin tradermal nodules varying in size and number. Differentials include calcification of epidermal or pilar cysts noted by the presence of keratinaceous debris. We present 2 cases of scrotal calcinosis at our institution.